EFFICACY AND SAFETY OF GABAPENTIN AND PREGABALIN IN CHEMOTHERAPY-INDUCED PERIPHERAL NEUROPATHY - N, MANJUSHREE; CHAKRABORTY, ANANYA; V, SHASHIDHAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Chemotherapy-Induced Peripheral Neuropathy (CIPN) occurs as a common Adverse Drug Reaction (ADR) of anti-cancer drugs. The prevalence varies from 10% to 100%. To date, there is no standard effective treatment protocol for this condition. However, the neuro-modulators such as gabapentin and pregabalin are increasingly being used to treat CIPN. With this background this study was undertaken to compare the efficacy and safety of gabapentin and pregabalin in CIPN. Methods: This study was conducted in the department of medical oncology at Vydehi Institute of Medical Sciences and Research Centre, Bengaluru. It was initiated after the approval from Institutional Ethics Committee. After obtaining written informed consent, the participants were randomized into two groups. Group A received gabapentin, 300 mg orally and Group B received pregabalin 75 mg orally; twice daily for 8 weeks. They were followed up at 2, 4, and 8 weeks. The intensity and quality of pain were assessed by visual analog scale (VAS) and pain quality assessment scale (PQAS). Safety was assessed by reported ADR. Data were analyzed using Student’s t-test and Mann–Whitney U-test. p=0.05 or less was considered as statistically significant. Results: Reduction in VAS and PQAS scores at 8 weeks was statistically significant in each group (p<0.0001). The ADR common to both the groups was drowsiness and sedation. The prevalence of ADR was more in the gabapentin group. Conclusion: Both gabapentin and pregabalin have similar clinical efficacy in the treatment of CIPN. The prevalence of ADR was higher in gabapentin group compared to pregabalin group.